New Models to Estimate Daytime and Shadow Length by Tracking the Shadow (International Journal of Psychosocial Rehabilitation, 2020)
In this study, models are presented to estimate the time from an object's shadow angle and estimate the shadow length from daytime. A stick length of 10 cm was used to measure the shadow length and shadow angle from 7 am to 5 pm on the 1st, 11th, 12th, 13th, 21st, 22nd, and 30th of September 2019. A new algorithm is presented to extract the shadow length and angle automatically from the work images quickly and with high accuracy. The presented algorithm results for both shadow length and shadow angle show a good matching of the measured data. The introduced models' results, for daytime and shadow length, have good agreement with the real data. The highest value of normalized mean square error (NMSE), used as a criterion for daytime data (from the first model) and real daytime, was 0.029%. The NMSE for the real shadow length and shadow length (online) was 0.011%, while the value (NMSE) between the real shadow length and the resulting model was less than 0.010%. This small percentage shows a good match in the estimation of the daytime and shadow length of an outdoor object at different times of day. The presented models can generalize globally.